2010
DOI: 10.1590/s0102-311x2010000100014
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and risk of oral and pharyngeal cancer: a case-control study in Rio de Janeiro, Brazil

Abstract: The study investigated IntroductionOral and pharyngeal cancer, grouped together, represent the sixth most common cancer in the world 1 . The annual estimated incidence is around 275,000 for oral and 130,300 for pharyngeal cancers excluding nasopharynx, with twothirds of these cases occurring in developing countries 1 . There is a wide geographical variation (approximately 20-fold) in the incidence of this cancer, and parts of Latin America and the Caribbean (including Brazil, Uruguay and Puerto Rico) are ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 21 publications
2
19
1
9
Order By: Relevance
“…Isto, pois não há dúvidas quanto à relevância da dieta hospitalar na preservação do estado nutricional dos pacientes/clientes, do seu papel co-terapêutico em doenças crônicas e agudas, além de ser uma prática que atende a atributos psicossensoriais e simbólicos de reconhecimento individual e coletivo. 3,4,5,14 Na análise da frequência dos cardápios, verificou-se que metade daqueles planejados é, de fato, executada (326), sendo grande parte (33%) deles relativos à dieta Padrão, também denominada Normal. A segunda dieta com maior número de cardápios foi a para Hemodiálise (20%), seguida pela dieta Hipossódica (15%), dieta Branda (14%) e as dietas IRA 40g (9%) e IRA 60g (9%).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Isto, pois não há dúvidas quanto à relevância da dieta hospitalar na preservação do estado nutricional dos pacientes/clientes, do seu papel co-terapêutico em doenças crônicas e agudas, além de ser uma prática que atende a atributos psicossensoriais e simbólicos de reconhecimento individual e coletivo. 3,4,5,14 Na análise da frequência dos cardápios, verificou-se que metade daqueles planejados é, de fato, executada (326), sendo grande parte (33%) deles relativos à dieta Padrão, também denominada Normal. A segunda dieta com maior número de cardápios foi a para Hemodiálise (20%), seguida pela dieta Hipossódica (15%), dieta Branda (14%) e as dietas IRA 40g (9%) e IRA 60g (9%).…”
Section: Discussionunclassified
“…Ademais, a dietoterapia é uma prática importante no decorrer da permanência hospitalar, uma vez que, atendendo os atributos psicossensoriais e simbólicos do reconhecimento do indivíduo, pode atenuar o sofrimento no período de ruptura de suas atividades cotidianas. 3,4,5 Neste sentido, as Unidades Funcionais dos Serviços de Nutrição e Dietética (UF-SND) podem viabilizar esse cenário, fornecendo uma alimentação adequada às necessidades nutricionais, sensoriais e emocionais dos pacientes/clientes, por meio de cardápios adequados, balanceados e atrativos. 6,7 Para que a atenção dietética se dê de forma integral, é necessário que haja planejamento e controle das etapas executadas pela unidade, a fim de se estabelecer meios para alcançar a qualidade dos processos na produção de refeições.…”
Section: Introductionunclassified
“…A diminuição de risco para o câncer oral pelo consumo de alimentos vegetais pobres em amido foi considerada provável em recente e extensiva revisão da literatura 10 . Estudos conduzidos no Brasil evidenciaram diminuição de risco para o consumo de alimentos vegetais 17,18 . Componentes das frutas e vegetais são indutores das GSTs 19 .…”
Section: Discussionunclassified
“…Over two-thirds of OPLC incidence and nearly 80 % of OPLC mortality occurs in developing countries [1]. OPLC incidence in developing countries, however, shows a large geographic variation, with such differences reaching up to 20 fold across different countries [2]. Underlying factors explaining these geographical variations are ethnic and racial differences which are postulated to play an important role in the etiology of OPLC [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated the relationship between dietary patterns and OPLC risk [2,7,[19][20][21][22][23][24][25][26][27][28] and offered valuable insight into how characteristic combinations of foods modulate OPLC risk. Overall, these studies showed a reduced OPLC risk for diets high in vegetables, fruits, and other fiber-rich foods as well as fish [29], characteristic of the 'Prudent' dietary pattern [2,7,25,26] and Mediterranean diets [19][20][21]27].…”
Section: Introductionmentioning
confidence: 99%